Thyroid function tests and its interpretation - Raj, KC Shiva (Journal of Pathology of Nepal, 2014)
Abstract: Thyroid diseases are among the most prevalent of medical conditions. In the patients with obvious features of hypothyroidism or hyperthyroidism thyroid function tests only confirm the diagnosis. Though TSH is widely used as a screening test in suspicion with thyroid disorder, many times TSH alone may be misleading. In this situation TSH along with T4 and T3 should be performed which will resolve the problem. However, thyroid function tests may not concord with each other. Discordant results between TSH, T4 and T3 may be because of various conditions like subclinical hypo- or hyperthyroidism, non-thyroidal illness, drugs etc. Beside that antibody interference and special condition like pregnancy may alter the thyroid hormone concentration. DOI: http://dx.doi.org/10.3126/jpn.v4i7.10318 Journal of Pathology of Nepal (2014) Vol. 4, 584-590